Therapeutic effects of stem cells in rodent models of Huntington's disease: Review and electrophysiological findings. (6th March 2018) - Holley, Sandra M.; Kamdjou, Talia; Reidling, Jack C.; Fury, Brian; Coleal‐Bergum, Dane; Bauer, Gerhard; Thompson, Leslie M.; Levine, Michael S.; Cepeda, Carlos
Summary: The principal symptoms of Huntington's disease (HD), chorea, cognitive deficits, and psychiatric symptoms are associated with the massive loss of striatal and cortical projection neurons. As current drug therapies only partially alleviate symptoms, finding alternative treatments has become peremptory. Cell replacement using stem cells is a rapidly expanding field that offers such an alternative. In this review, we examine recent studies that use mesenchymal cells, as well as pluripotent, cell‐derived products in animal models of HD. Additionally, we provide further electrophysiological characterization of a human neural stem cell line, ESI‐017, which has already demonstrated disease‐modifying properties in two mouse models of HD. Overall, the field of regenerative medicine represents a viable and promising avenue for the treatment of neurodegenerative disorders including HD.